Experimental insights into the formation and characterization of iodine oxide aerosols - Mariam,; Joshi, Manish; Nakhwa, Amruta; Khandare, Pallavi; Soumen, Samanta; Khan, Arshad; Sapra, B. K. (Frontiers in Nuclear Engineering, 2025)
IntroductionA significant quantity of radioactive iodine is expected to be released following severe nuclear reactor accidents. Recent studies have shown that among various species expected, iodine oxides (IxOy) are less explored but play a crucial role in nuclear safety assessments due to their impact on source term evaluation. Therefore, this study was designed to generate and characterize iodine oxides in a laboratory scale setup.MethodsExperiments were conducted at room temperature and ambient relative humidity using an I2 concentration of ∼1 ppm and an O3 concentration of ∼30 ppm inside a controlled chamber. The reaction kinetics were determined by continuously monitoring O3 concentration. While many previous studies have relied on the radioactive iodine tracers and gamma spectroscopy, this study adopts an alternative approach by analysing ozone decay as a proxy for iodine oxidation. The generated iodine oxide aerosols were characterized for their physical and chemical properties. Impactors and gross samplers were used to collect aerosols, giving particle mass size distribution and total mass concentration, respectively. Particle morphology and chemical composition were determined using a scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS).Results and discussionThe reaction kinetics showed that ozone decay followed first-order kinetics with a high correlation (R2 > 0.99). The particles were found to have I2O5 chemical species with varied shapes, from small porous cloud-like structures to large rod-shaped particles. The findings provide valuable insights into iodine oxidation under environmentally relevant conditions, bridging knowledge gaps in source term estimation and contributing to the enhancement of accuracy of the modeling codes for nuclear safety applications.